Impact of emergency department discharge stream short stay unit performance and hospital bed occupancy rates on access and patient flowmeasures: A single site study. (16th April 2017) - Shetty, Amith L; Teh, Caleb; Vukasovic, Matthew; Joyce, Shannon; Vaghasiya, Milan R; Forero, Roberto
Abstract: Objective: The ED discharge stream short stay units (EDSSUs) aim to facilitate patient flows through EDs. We investigate the relationship between EDSSU census and hospital bed occupancy rates (BORs) on National Emergency Access Target (NEAT) performance and did‐not‐wait (DNW) rates at a tertiary metropolitan adult ED in Sydney, Australia. Methods: We collated data for all ED presentations between 1 January 2012 and 31 December 2014. Daily ED, EDSSU census and ED‐accessible hospital BORs were tabulated with daily ED NEAT performance and DNW rates. Non‐parametric regression analyses was conducted on cohorts of appropriate, inappropriate, successful and failed EDSSU admissions based on local admission policies and BOR for NEAT and DNW outcomes. Results: Among all presentations ( n  = 192 506) during the study period, 43.8% of patients were admitted in hospital including 10.4% for EDSSU ( n  = 20 081). Analyses reveal modest positive correlation of EDSSU admissions with NEAT performance ( τ  = 0.35, P  < 0.001) and weak negative correlation with DNW rates ( τ  = −0.29, P  < 0.001). These associations were more pronounced on days when BOR >100% ( τ  = 0.39 and τ  = −0.36, P  < 0.001). BOR of >100% were associated with reduced EDSSU admits, NEAT performance and increased DNW rates ( P  < 0.001). Appropriate EDSSU admissions had shorter EDSSU length of stay than inappropriate EDSSU admissions (350 vs 557 min, median difference −158 min, P  < 0.001). Conclusion: Appropriate use of EDSSU provides effective conduit for ongoing patients' management beyond mandated timelines. Health systems should focus on reducing hospital BORs to mitigate exclusive ED pressure to deliver NEAT performance targets.